2010
DOI: 10.1243/09544062jmes1735
|View full text |Cite
|
Sign up to set email alerts
|

Flow measurements across an automotive catalyst monolith situated downstream of a planar wide-angled diffuser

Abstract: Flow measurements are presented across an automotive catalyst monolith situated downstream of a planar wide-angled diffuser. Particle image velocimetry measurements were obtained in the diffuser and the flow distribution within the monolith was obtained from hot wire anemometry at the monolith exit. Flow separation at the diffuser inlet resulted in the formation of a jet that traversed the diffuser before spreading just prior to entering the monolith. The jet featured a potential core and saddle-type velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Re is defined as U in d h / v where U in is the mean velocity at the diffuser inlet, d h the hydraulic diameter of the nozzle (38.4 mm) and v the kinematic viscosity. The shear layers at the sides of the jet are clearly shown as are the saddle-shape profiles in its potential core; similar features have been observed by Quadri et. al.…”
Section: Steady Flowsupporting
confidence: 83%
See 1 more Smart Citation
“…Re is defined as U in d h / v where U in is the mean velocity at the diffuser inlet, d h the hydraulic diameter of the nozzle (38.4 mm) and v the kinematic viscosity. The shear layers at the sides of the jet are clearly shown as are the saddle-shape profiles in its potential core; similar features have been observed by Quadri et. al.…”
Section: Steady Flowsupporting
confidence: 83%
“…Ilgner et al (2001), made PIV measurements upstream of an auto-thermal gas reformer but significant image distortion due to wall curvature restricted the field of view where reliable data could be obtained. Using a planar diffuser optical distortion was minimised by Quadri et al (2009a). By comparing the upstream flow field (PIV) with that measured downstream of the monolith using HWA it was demonstrated that the monolith radically redistributes the flow as it enters the channels.…”
Section: Introductionmentioning
confidence: 99%
“…So, to explain the present results more comprehensibly, we should discuss the flow in the catalyticconverter diffuser part which will bring us deeper and fruitful understanding, engineering innovation and so on. Recently, Quadri et al (2009) and Yamin et al (2013) have visualised the flow in the catalytic-converter diffuser part using a twodimensional model for steady and pulsating flows, respectively. While they are in the no-flow-deflector case of course, they have shown the importances of the catalyst-converter substrate part, the frequency of flow pulsation and so on.…”
Section: Velocity Profilementioning
confidence: 99%